Using the Health Belief Model to explore why women decide for or against the removal of their ovaries to reduce their risk of developing cancer - Anne Herrmann; Alix Hall; Anthony Proietto (BMC, 2018)
Abstract Background Women at an increased risk of ovarian cancer often have to decide for or against the surgical removal of their healthy ovaries to reduce their cancer risk. This decision can be extremely difficult. Despite this, there is a lack of guidance on how to best support women in making this decision. Research that is guided by theoretical frameworks is needed to help inform clinical practice. We explored the decision-making process of women who are at an increased risk of developing ovarian cancer and had to decide for or against the removal of their ovaries. Methods A qualitative study of 18 semi-structured interviews with women who have attended a cancer treatment centre or cancer counselling and information service in New South Wales, Australia. Data collection and analysis were informed by the Health Belief Model (HBM). Data was analysed using qualitative content analysis. Results The paper describes women's decision making with the help of the four constructs of the HBM: perceived susceptibility, perceived severity, perceived benefits, and perceived barriers. The more anxious and susceptible women felt about getting ovarian cancer, the more likely they were to have an oophorectomy. Women's anxiety was often fuelled by witnessing family members suffer or die from cancer. Women considered a number of barriers and potential benefits to having the surgery but based their decision on "gut feeling" and experiential factors, rather than statistical risk assessment. Age, menopausal status and family commitments seemed to influence but not determine women's decisions on oophorectomy. Women reported a lack of decision support and appreciated if their doctor explained their treatment choice, provided personalised information, involved their general practitioner in the decision-making process and offered a second consultation to follow-up on any questions women might have. Conclusions These findings suggest that deciding on whether to have an oophorectomy is a highly personal decision which can be described with the help of the HBM. The results also highlight the need for tailored decision support which could help improve doctor-patient-communication and patient-centred care related to risk reducing surgery in women at an increased risk of ovarian cancer.